Síntese de novos sulfetos vinílicos derivados de 3- carbaldeído indóis via reações de Wittig-Horner - Brites, Nathan Pinto (2023)
This work describes the synthesis of 15 novel vinyl sulfides based on a series of substituted indoles via Wittig-Horner reaction. The synthesized products were obtained in yields ranging from 255 to 93%. Initially, different substituted indole-3-carbaldehydes 1a-f were reacted with arylsulfide-functionalized phosphine oxides 2a-b, employing NaH as base and THF as solvent, at reflux temperature for 3 to 24 h, leading to the obtention of vinyl sulfides 3a-n. On the other hand, this same method was not efficient for obteining vinyl sulfides based on indoles substituted with N-Boc- or N-tosyl-groups, leading to low yields and to byproducts formation. Subsequently, the previously developed protocol was employed for the synthesis of non-symmetrical substituted bisvinyl derivatives 4a-c, employing NaH as base, THF as solvent and HMPA, at reflux temperature, for 5 to 24 h. Under these conditions, four new products were obtained in 70% to 81% yields. The developed procedure furnished the vinyl sulfides as an isomeric mixture, with preferential formation of, respectively, E and E,E geometric isomers. From this result, the same reaction conditions were tested by employing bismethylene sulfide phosphinoxide derivative 2e and two equivalents of indole-3- carbaldehyde 1a as reactants to synthesize a bis-indolyl-vinyl sulfide 5. The reaction was conducted at reflux temperature for 5 h, furnishing the product in 71% yield. Thereafter, a method for the synthesis of alkynyl-functionalized vinyl sulfides 6a-b via Wittig-Horner reaction was developed. In this reaction, an alkynylsulfide- - functionalized phosphinoxide derivative 2f and indole-3-carbaldehydes 1 were employed as reagents. The reactions were conducted in THF, employing NaH as base at reflux temperature for 4 h. The vinyl sulfides were obtained in 78% to 89% yields, with good stereoselectivity. This method furnished two alkyne-functionalized vinyl sulfides as an isomeric mixture, with preferential formation of geometric isomers with E-configuration. N-Benzyl-substituted indole derivative 6a was obtained as a 91:9 E:Z mixture, while N-methyl-substituted indole derivative 6b was obtained as a 70:30 E:Z mixture.